Aktualisasi Nilai BerAKHLAK dalam Transformasi Digital Tata Kelola Laboratorium Tarbiyah: Studi Pengembangan E-Book Panduan Praktikum di PTKI - Nur Azizah; Deviana Setia Ningrum (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2025)
Digital transformation in university governance has become a strategic imperative in the era of technological disruption, requiring systemic adaptation across academic support services, including laboratory management. This study aims to examine strategies for optimizing the Tarbiyah Laboratory services at the Faculty of Tarbiyah and Teacher Training, UIN Mahmud Yunus Batusangkar, through the development of an e-book practicum guide integrating the core values of ASN BerAKHLAK. The study is motivated by the absence of standardized and well-documented operational procedures, which has resulted in service inefficiencies and administrative ambiguity. Employing a Participatory Action Research (PAR) design based on the Kemmis and McTaggart cycle, the research began with problem identification using the APKL technique. The findings indicate that the lack of a practicum guide represented the most critical issue and was addressed through the development of an e-book containing Standard Operating Procedures for Tahsin, Tahfidz, and Religious Practice activities. The implementation of this digital guide enhanced operational efficiency, information accessibility, and user satisfaction, while simultaneously facilitating the internalization of service orientation, accountability, competence, and collaboration. The study recommends expanding digitalization across academic service instruments to support sustainable good governance in Islamic higher education institutions.